ANALISIS PERSEPSI KONSUMEN TERHADAP PERCEIVED QUALITY DALAM UPAYA PENGEMBANGAN STRATEGI PRODUK USAHA MASKER (STUDI KASUS PADA USAHA MASKER DIE WOLKE) - Ghifari Laili Rizqy; Arianis Chan; Cecep Safa’atul Barkah; Pratami Wulan Tresna (Jurnal Manajemen, 2021)
This research aims to discover the level of product's development needs expected by Die Wolke's consumers. Furthermore, this research also wants to know what product's development is expected by consumers. And the last, this research also wants to create a product development strategy based on the level of Product’s development needs of Die Wolke's consumers by using Marketing Mix 7P which focuses on product. the participants for this research are Die Wolke's consumers from august to november (n: 106). For the sample, the researcher use simple random sampling with the minimum sample size determined by slovin formula (n: 65). The results showed that Die Wolke consumers prioritize product's development in mask's design.